2006
DOI: 10.1002/pola.21703
|View full text |Cite
|
Sign up to set email alerts
|

Starch‐graft‐copolymer latexes initiated and stabilized by ozonolyzed amylopectin

Abstract: A method is presented for synthesizing surfactant-free latexes comprising a starch-graft-vinyl polymer, (1) starting with a suspension of the highly branched starch amylopectin, either native or degraded, (2) then using ozonolysis to create free-radical initiation sites on this amylopectin scaffold, and (3) finally adding the monomer and inducing polymerization. The ozone simultaneously thins the starch and creates initiating/grafting sites on the starch, from which starch-graft-copolymer latexes can be grown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 25 publications
2
37
0
1
Order By: Relevance
“…Latexes 1 to 5 were ultrasonicated (Sonics Vibracell, 30%, 5 min), after which their viscosities reduced to approximately that of the equivalent raw starch suspensions (5–30 cP for 1–5 wt % starch suspensions respectively). This is strong evidence of the “scaffold” structure of the latex and the associated gelation mechanism described in detail in our previous paper 3. Native amylopectin can degrade under shear 28.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Latexes 1 to 5 were ultrasonicated (Sonics Vibracell, 30%, 5 min), after which their viscosities reduced to approximately that of the equivalent raw starch suspensions (5–30 cP for 1–5 wt % starch suspensions respectively). This is strong evidence of the “scaffold” structure of the latex and the associated gelation mechanism described in detail in our previous paper 3. Native amylopectin can degrade under shear 28.…”
Section: Resultssupporting
confidence: 73%
“…This thinning appears to be necessary to avoid gelation of the latex under the experimental conditions used in the past. This article extends previous work, based on ozone grafting/initiation,3 to a Ce 4+ ‐based method for producing stable synthetic polymer latexes with a high proportion of high molecular weight starch grafted to the latex particles.…”
Section: Introductionsupporting
confidence: 72%
“…Yeng et al 11 reported acrylamide modified sago starch which was utilized as paper coatings to improve paper surface physical and mechanical properties. De Bruyn et al 12 adopted ozonolyzed AP as initiator and stabilizer to initiate the graft copolymerization of St, BA, and vinyl acetate onto starch to obtain starch‐ graft ‐copolymer surfactant‐free latexes. De Bruyn et al 13 used Ce 4+ initiator and AP stabilizer to successfully produce native wx starch grafted poly(styrene‐butyl acrylate‐vinyl acetate) surfactant‐free latexes.…”
Section: Introductionmentioning
confidence: 99%
“…Starch can be grafted to produce new materials with properties that combine the advantages of natural and synthetic polymers. Published studies have proven that the application properties of the starch graft copolymer are better than the commonly used mixtures of synthetic polymer latex and starch [10,11]. Furthermore, replacing part of the synthetic monomer with OS can reduce the cost of latex and benefit the environment because of the low cost and biodegradability of starch.…”
Section: Introductionmentioning
confidence: 99%